(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The author discusses the matter of contemporary culturological science considering such aspects as history of formation of culturological principles, methodology and organization of functional essence of general philosophical theoretical knowledge. In this context axiological universals, historic-civilizational constant, ethno-demographic, artistic-voluntative, and other parts of philosophy of culture are analyzed. Throughout the genesis process humanity has developed an instinct to abide by traditional tested ways, and to stand against something unknown. This conservative phenomenon is an explanation of various theories of scientific and cultural crisis (so called “end of history”) which frequently take place in philosophical conceptions. The idea originated from “philosophy of despair” of Dutch Christian humanist Søren Kierkegaard which contributed to work of other famous philosophers such as O. Spengler, H. Zimmel, E.Husserl, T. Lessing, P. Sorokin, and others. The idea of temporality of every event served as a basis for the philosophical contemplation over the cultural crisis. As a consequence of this temporality scientific progress and classical rationalism of Renaissance and the period of early modern Europe steadily became history followed by the age of intellectual labor concentrated on making life easier, more practical and comfortable. The last concept of cultural development belongs to Postmodernism movement caused directly by formation of apprehension of cultural crisis. As it stated by followers of this movement (e.g. M. Foucault, J. Lyotard), devaluation of spiritualism in society shows us what mankind really desires: mere consumerism, while art and culture are, basically, to entertain audience. Concept of postmodernism is unexpected: total denial of society’s sustainable structure, artistic chaos, proclamation of “dialogic imagination” (term coined by philosopher M. Bahtin), demolishing of authorities, irony, critical analysis of IT. Keywords: philosophy of culture, history, individual, spirituality.